Contextualising IPAS learning through local wisdom: A culturally rooted PJbL model for primary education - Dyan Wulan Sari HS; Darinda Sofia Tanjung; Rumiris Lumban Gaol; Nova Florentina Ambarwati; Meikardo Samuel Prayuda; Dinesh Elango (Laboratorium Program Studi Pendidikan Guru Sekolah Dasar, 2025)
The present study analyses the needs and readiness for implementing Science and Social Studies (IPAS) learning based on Project-Based Learning (PjBL) integrated with local wisdom values, particularly the Toba Nauli cultural philosophy, at the elementary school level. Motivated by the low science literacy of Indonesian students as revealed in the 2022 PISA results and the lack of contextual relevance in IPAS content, the research adopts a mixed-methods design combining qualitative and quantitative approaches. Data were collected through interviews, classroom observations, document analysis, and Likert-scale questionnaires involving 20 teachers and 40 students across four elementary schools in Medan. The research results show that teachers have a positive perception of the importance of PjBL and science literacy, as well as a high belief in the relevance of Toba Nauli values in IPAS learning (M = 4.20; SD = 0.68). However, the limitations of teaching modules, lack of training, and low use of local media have made cultural integration in learning not optimally implemented. On the other hand, students show high enthusiasm for project-based learning. However, their actual experience with learning incorporating local culture is minimal (only 15% of students reported having experienced it). These findings indicate a significant potential yet to be realised within the current IPAS learning system. Therefore, this research recommends developing a PjBL-based IPAS learning model that incorporates the Toba Nauli philosophy as a foundation for the local context to enhance students' science literacy in a meaningful, contextual, and culturally rooted manner. These findings are expected to serve as a conceptual and empirical foundation in designing transformative learning innovations in elementary schools.